Maksimisasi Keuntungan Usahatani Cabai Dan Tomat Dengan Kendala Faktor Produksi Di Desa Pombewe, Kecamatan Sigi Biromaru, Kabupaten Sigi - I Ketut Rembun; Max Nur Alam; Saharia Kassa Saharia Kassa (Mitra Sains, 2016)
The aim of research to analyze the actual profit, profit maximization, and the sensitivity of chilli and tomato farm in the village of Pombewe, District Sigi Biromaru, Sigi. The sampling technique conducted a census that as many as 17 people. Data collected by interview using interview guideline. Secondary data obtained from the village monograph, BPS and various journals. The results using the actual profit earned revenue analysis of chilli and tomato farming in aggregate on an area of 0.69 Ha reached Rp 43.331.876,47, and partially chili farm with an area of 0.33 Ha reached Rp 23.280.509,12 and tomato farming with an area of 0.36 Ha reached Rp 20.051.387,35. Analysis using linear program obtained maximization profit of Rp 129 599 700, - with chilli farming area of 1.03 Ha and 1.02 Ha of farming tomatoes. Sensitivity analysis of optimization that has been achieved is determined by the change in the willingness of each seed seeds chili> 16.20 sachet or tomato seeds> 29.72 sachet.